INCREASING STUDENT’S SELF CONFIDENCE IN ENGLISH SPEAKING SKILL BY ZACH ON THE TIKTOK APPLICATION AT XI GRADE OF SMA NEGERI 2 PERCUT SEI TUAN - Ayu Putri Ani Sagala; Jefri Mando Sinurat (Jurnal Scientia, 2022)
Abstarct This thesis focuses on knowing the effect of speaking with zach on the tik tok application on students' confidence in speaking English at SMA Negeri 2 Percut Sei Tuan. This study was conducted with a quantitative design. The population of this study were eleventh grade students at SMA Negeri 2 Percut Sei. Tuan. The author wants to increase students' confidence in speaking English by applying the technique of speaking English with zach on the tik tok application. The sample method of this research is the eleventh grade students as many as 34 students. The data collection instruments are Questioner 1 and Questioner 2. Data collection is carried out by giving 2 questionnaires at different times. The result of this research found that describes people could improve students' self-confidence in speaking. It was proved by the mean score of the students in questionnaire one (Q1) is 67.88 (precisely self-confidence level) and students mean score in questionnaire two (Q2) is 79.76 (medium self-confidence level). It means that the students have shown raising the self-confidence level from precisely into the medium.